Wildlife of the caribbean coast of Nicaragua / Christopher Jordán - Jordan, Christopher (Estados Unidos de América: Michigan State University, 2009)
Thus, we worked hard to collect local knowledge of and anecdotes about some of the more common, well-known, and locally significant animal species in the RAAS, we then combined this with information available in the scientific literature and information, generated through our own research to create a quide that is both locally relevant and scientifically accurate and educational.
Portada ilustrada
Col. Agro
Keywords: 1. RECURSOS BIOLOGICOS 2. WILDLIFE-CARIBBEAN COAST NICARAGUA 3. AGROFORESTAL